2022
DOI: 10.4102/ajopa.v4i0.63
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of the UCLA loneliness scale in South Africa: Factor structure and dimensionality

Abstract: This study examines the generalisability of the University of California Los Angeles Loneliness Scale Version 3 (UCLA-LS3) in a South African sample of young adults. In particular, it examined the normative data, reliability, and factor structure of this scale. The participants were young adults (N = 337) who were randomly sampled from a university population and they responded to the UCLA Loneliness Scale. It was found that the sample had higher loneliness scores than those reported in the literature, potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…For example, the scale has robust psychometric properties, such as scale score reliability, test-retest reliability, convergent validity, and factorial validity, in a Farsi version among healthy participants [38]. Similar psychometric findings have been reported for the Turkish version [39], Japanese version [40], Danish version [41], English version [42,43], Spanish version [44] and many other language versions [42] across different populations (e.g., older people, adolescents and mothers). However, although the UCLA Loneliness Scale (Version 3) has been translated into Chinese, to the best of the present authors' knowledge, it has never been validated among a Taiwanese population and no language version has ever been psychometrically evaluated with sexual-minority men.…”
Section: Introductionsupporting
confidence: 60%
“…For example, the scale has robust psychometric properties, such as scale score reliability, test-retest reliability, convergent validity, and factorial validity, in a Farsi version among healthy participants [38]. Similar psychometric findings have been reported for the Turkish version [39], Japanese version [40], Danish version [41], English version [42,43], Spanish version [44] and many other language versions [42] across different populations (e.g., older people, adolescents and mothers). However, although the UCLA Loneliness Scale (Version 3) has been translated into Chinese, to the best of the present authors' knowledge, it has never been validated among a Taiwanese population and no language version has ever been psychometrically evaluated with sexual-minority men.…”
Section: Introductionsupporting
confidence: 60%
“…The satisfactory reliability (α = 0.81 and 0.92) of the UCLA-LS was demonstrated in two samples of young adults in South Africa [26,52]. The dimensionality of the UCLA-LS was confirmed by Pretorius in South Africa [53], who reported that it is best conceptualized as a total scale with three subscales.…”
Section: Instrumentsmentioning
confidence: 79%
“…Two South African studies reported acceptable reliability (0.81 and 0.92) for the UCLA-20 when used with student samples [46,47]. The structure of the UCLA-20 was also confirmed using confirmatory factor analysis (CFA) with ancillary bifactor indices in a South African study [30].…”
Section: Instrumentsmentioning
confidence: 80%
“…Other studies have found mixed results. One-factor [25], two-factor [26], three-factor [27,28], and bifactor solutions [29,30] have been reported.…”
Section: Introductionmentioning
confidence: 99%